The inverse function of is where , and are constants. What is
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
It's more intuitive (at least for most people) if we swap the letters x and y on our relation before starting the calculation, we get x = y − 3 + 6 . We do this because on the inverse function the the roles are interchanged, hence now the task is to clear the variable x
x = y − 3 + 6 ( x − 6 ) 2 = y − 3 x 2 − 1 2 x + 3 9 = y
Looking at the first equation (or the graph) it's clear that the smallest value x can take is 6 when the square root is 0 , hence a + b + c = 6 − 1 2 + 3 9 = 3 3